Os Condomínios horizontais fechados em Anápolis/GO : a produção do espaço intraurbano (2000-2016) - Guimarães, Pollyana Martins Santana (2017)
Closed Horizontal Condominiums (CHF's), a phenomenon characteristic of large cities and metropolises, have spread to other scales, reaching also average cities, which play an intermediary role in the urban network, exerting a strong influence on small cities. The implantation and the constitution of the CHF's in average cities show differences from those found in the metropolises, because due to the particularities of size, population and lifestyles, they attend to other urban dynamics. Increasingly, these projects aimed at self-segregated housing have accentuated the scenario of socio-spatial segregation in contemporary cities. Stimulators of new socio-spatial practices and new habits of living, CHF's come under different typologies, coming from the performance of different social actors. Thus, this paper aims to discuss the specificities of CHF's in medium-sized cities, highlighting the case of Anápolis/GO, located in Goiânia-Anápolis-Brasília Hub.